PARTICIPATORY ECOLOGICAL THEOLOGY: The Ecological Theological Perspective of John B. Cobb Jr. - Cui, Renzhong (QUAERENS: Journal of Theology and Christianity Studies, 2024)
John B. Cobb Jr., a well-known theologian, philosopher, and environmentalist in the United States, has developed his participatory ecological theology from process philosophy to process theology. Some scholars believe it belongs to a distorted form of anthropocentrism, while others suggest it belongs to biocentrism. This study seeks to explore how participatory ecological theology from the perspective of John B. Cobb, Jr. based on a participatory ecological approach to the discourse of environmental ethical methods, especially from a theological perspective. However, through Cobb’s attention to and exploration of environmental crises and interactions with other environmentalists, his ecological theology is shown to be a new form of participatory ecological theology that recognizes the intrinsic value of all existence and affirms the participatory ecological order of nature. He challenges the traditional Christian doctrine of “dominion”. He points to a more responsible concept for humanity, that is, to serve all parts of the natural world as responsible creations, just as serving God.